Penerapan Komunikasi Penyuluhan Pertanian pada Lahan Basah di Wilayah Gantiwarno, Klaten, Jawa Tengah - Baihaqi, Muhammad Ihsan; Christin, Maylanny (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Indonesia is an agricultural country where 40% of the population has a livelihood in agriculture. The agricultural sector plays an important role in the development of the national economy, including the regional economy. The agricultural sector itself has a function as a provider of food for the community, reducing poverty, pioneering employment, and as a source of community income. In the agricultural sector, someone is needed to communicate agricultural technology programs and developments to the farming community so that they can facilitate the agricultural sector. Agricultural technology has had a positive impact on economic welfare and made facilities and infrastructure for farming and maintenance of agriculture easier. Gantiwarno is one of the sub-districts where most of the agricultural land is wetland. Wetlands are lands whose properties or types of soil are saturated with water, and their ecosystems are controlled by water. land whose nature or type of soil is saturated with water. This study uses a constructivism paradigm with a descriptive qualitative approach and uses data collection techniques with in-depth interviews, observation, and documentation. Researchers conducted interviews with 4 key informants consisting of farmers, UD. Setiti Tani farm shop owners, UD farm shop employees. Setiti Tani and 1 expert informant to complete the data. The researcher draws the conclusion that agricultural extension communication on wetlands in the Gantiwarno area, Klaten, Central Java uses the SMCR communication method, namely: source as a source for giving messages when counseling is carried out, messages that must be conveyed in good and easy-to-understand language, channels or media it is very important to facilitate the dissemination in agricultural extension, the receiver or receiver of the message must be able to receive the message properly so that he is able to direct it in a good direction from before.